The subject of Exoticism: Victor Segalen's Equipée - Michel, Andreas (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
This essay analyzes Victor Segalen's Equipée in conjunction with Segalen's exploration of the notion of "exoticism" as a philosophical concept. It demonstrates how exposure to radical difference (the "exotic") leads to a destabilization of the self-same subject which is made and unmade in the contact with otherness and how Equipée enacts Segalen's vision of the subject as a process of continuous emergence.